Current State of Processing of Seed Wheat in the Republic (Journal of Pharmaceutical Negative Results, 2022)
The foundation of obtaining a high yield and quality products from agricultural crops depends on the seed, and therefore the cultivation and processing of seeds, the control of quality indicators of the variety and sowing of the crop are of particular importance for seed production.After gaining grain independence in the Republic of Uzbekistan, much attention is paid to seed production. Given this, the improvement of seed processing enterprises is one of the urgent tasks, since the cleaned, sorted seed material is considered the key to a good harvest next year.Based on the results of the analysis of existing technological lines for processing seed wheat grain, on the assumption of the conditions of the Bukhara region, the need to improve the technological scheme for processing seed wheat grain, based on the technological features of localized wheat seeds grown in the conditions of the Bukhara region, has been scientifically substantiated.